Modeling the relationships among psychological immunity, mindfulness and flourishing of university students - Essa, Eman Khaled (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2020)
The aim of this study is to examine the relationship among psycho-immunity, mindfulness and flourishing of university students. To achieve this a battery of instruments was applied to 140 Faculty of Education of Damanhour University students. The study tests a model for analyzing the effects of psycho-immunity and mindfulness on psychological flourishing. The findings of the study show evidence in favor of the influence of psycho-immunity and mindfulness as factors in the prediction of flourishing. finally, the results assert the importance of psycho-immunity and mindfulness in achieving flourishing.